Inside Cover: Efficient Biomimetic Hydroxylation Catalysis with a Bis(pyrazolyl)imidazolylmethane Copper Peroxide Complex (Chem. Eur. J. 49/2015). Issue 49 (1st December 2015) - Wilfer, Claudia; Liebhäuser, Patricia; Hoffmann, Alexander; Erdmann, Hannes; Grossmann, Oleg; Runtsch, Leander; Paffenholz, Eva; Schepper, Rahel; Dick, Regina; Bauer, Matthias; Dürr, Maximilian; Ivanović‐Burmazović, Ivana; et al.
Abstract : A catalytic vortex producing quinones was realized by a (μ‐η 2 :η 2 )‐peroxo dicopper(II) core resembling the active centre of tyrosinase. This biomimetic species is stabilised by a new bis(pyrazolyl)imidazolylmethane ligand. Kinetic experiments show that this peroxide species mediates phenole hydroxylation with almost biological speed. This enhancement was achieved by exchanging a pyridinyl donor against the imidazolyl donor. For more details, see the Full Paper by S. Herres‐Pawlis and co‐workers onpage 17639 ff.